Community Economic Priorities as Gating Mechanisms in Urban Tourism: Empirical Evidence from Surabaya - Astariadi Kurniawan; Mas Dedi Hidayatullah; Nur isra Resyah; Rahmat Hidayat; Saskia Ariani (CV. Science Tech Group, 2026)
Urban tourism policy in emerging Southeast Asian cities tends to operate along separate tracks. Heritage preservation, destination marketing, MSME development, and employment policy seldom intersect in practice, even when planning documents gesture toward coordination. This study examines whether a more deliberate form of policy integration, one anchored to the economic priorities residents actually hold, can offer a sturdier path for cities such as Surabaya than the prevailing sector-by-sector orthodoxy. The study combines a quantitative survey of 800 Surabaya residents conducted during October 2024 (multistage random sampling, margin of error ±3.5 percent, 95 percent confidence level) with documentary analysis of municipal tourism instruments and structured observation across five administrative regions. Cross-tabulation analysis reveals perception variation across demographic strata. Correlation analysis maps relationships among prioritisation dimensions. Policy mapping identifies the operational seams where intended integration falters. Economic improvement dominates community priorities at 57.8 percent overall, rising to roughly 71 percent among economically precarious populations. Community endorsement of tourism initiatives proved conditional rather than enthusiastic; it depends on visible job pathways and MSME integration. Culinary tourism enjoys broad support (76.3 percent); heritage development sits at 68.9 percent; generic destination marketing trails at 51.7 percent. The most consequential finding concerns the gap separating tourism policies as articulated from tourism policies as residents consider deliverable. This implementation gap is best understood not as a perception problem but as a design problem demanding architectural integration. Beyond local livelihoods, integrating community economic priorities into urban tourism policy supports sustainable urban development, eases pressure on natural resources by diversifying economic opportunities, and advances Sustainable Development Goal 11 (Sustainable Cities and Communities) and Goal 8 (Decent Work and Economic Growth) in emerging Southeast Asian cities.